Quantitative Expression of Key Cancer Markers in the AS-30D Hepatocarcinoma Model - Briones-Orta, Marco A.; Delgado-Coello, Blanca; Gutiérrez-Vidal, Roxana; Sosa-Garrocho, Marcela; Macías-Silva, Marina; Mas-Oliva, Jaime (Frontiers in Oncology, 2021)
Hepatocellular carcinoma is one of the cancers with the highest mortality rate worldwide. HCC is often diagnosed when the disease is already in an advanced stage, making the discovery and implementation of biomarkers for the disease a critical aim in cancer research. In this study, we aim to quantify the transcript levels of key signaling molecules relevant to different pathways known to participate in tumorigenesis, with special emphasis on those related to cancer hallmarks and epithelial-mesenchymal transition, using as a model the murine transplantable hepatocarcinoma AS-30D. Using qPCR to quantify the mRNA levels of genes involved in tumorigenesis, we found elevated levels for Tgfb1 and Spp1, two master regulators of EMT. A mesenchymal signature profile for AS-30D cells is also supported by the overexpression of genes encoding for molecules known to be associated to aggressiveness and metastatic phenotypes such as Foxm1, C-met, and Inppl1. This study supports the use of the AS-30D cells as an efficient and cost-effective model to study gene expression changes in HCC, especially those associated with the EMT process.